Pengaruh Rasio Penambahan Acticomp Terhadap Degradasi Struktur Morfologi Tandan Kosong Kelapa Sawit Pada Proses Pengomposan Metode Windrow - Nurfajri, Nabila; Yenie, Elvi; Edward, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Oil palm empty fruit bunches (OPEFB) is a solid waste that significantly produced by palm oil mills. The main content of OPEFB is lignocellulose. High lignin in OPEFB cause the lenghth time of OPEFB decompositition. The decomposition process can be accelerated by the addition of decomposers, such as acticomp. Therefore, this study aimed to analyze the degradation of structure morphology OPEFB also composting time and C/N ratio by the addition of acticomp. This research method using three variations of the ratio addition acticomp to 100 kg OPEFB composted, 0.5 kg acticomp, 1 kg acticomp and 1.5 kg acticomp. The comsposting process using windrow composting system. The results were obtained the damage of OPEFB morphological structure and the decreasing ratio of C/N whereas 1.5 kg acticomp/100 kg as the biggest within 30 days. C/N ratio reached 19.67, in accordance with the regulation of the quality standards 28/Permentan/SR.130/5/2009.Keywords: acticomp, OPEFB, degradation of OPEFB, morphological of OPEFB, windrow composting